Gene network and canonical pathway analysis in canine myxomatous mitral valve disease: A microarray study. Issue 1 (April 2015) - Lu, C.-C.; Liu, M.-M.; Culshaw, G.; Clinton, M.; Argyle, D.J.; Corcoran, B.M.
Highlights Microarrays were used to analyse transcript changes in canine myxomatous mitral valve disease (MMVD). In total, 591 differentially expressed genes were identified with 322 up-regulated and 269 down-regulated. Data suggest contribution of endothelial-to-mesenchymal transition to disease pathogenesis. Data will allow for hypothesis-driven research to understand MMVD.